Numerical Analysis on the Structure Type and Mechanical Response of Tunnel Crossing Active Reverse Fault - Xianmin Han; Wenjiang Li (Geofluids)
Faulting would result in ground deformation and even damage to the tunnel structure. Thus, special structural designs should be made when the tunnel passes through an active fault. A single-track railway tunnel crossing a reverse fault is used to study the suitable structure type. In this paper, antidislocation structural measures such as reasonable segment length of articulated lining, cross-section shape, and thickness of lining are discussed through the numerical simulation. Firstly, the rational segment length of the articulated lining is confirmed. Stress and deformation behavior of articulated lining are also analyzed after the fault move. Then, the antifault effect of two kinds of cross-section shapes and three different lining thicknesses are compared. Researches show that the segment length of the articulated lining could be confirmed by the longitudinal distribution of maximum bending moment of lining after faulting. There are apparent stress concentrations occurring in the lining segment crossing the fault plane, and serious damage appears in the vault and wall waist of the tunnel. The horseshoe section with big curvature inverted arch is recommended to a single-track railway tunnel across an active fault. Simply increasing lining thickness is not suggested in a tunnel structure design crossing the active fault. The size of tunnel expansion and the minimum length of segment across fault plane can be geometrically determined according to fault dislocation magnitude and dip angle.